Antioxidant and Antiglycation Activity of Rhizosphere and Endophytic Actinobacteria of Xylocarpus granatum - Alifian Ariansyah; Irmanida Batubara; Yulin Lestari; Saat Egra (Biosaintifika: Journal of Biology & Biology Education, 2019)
Utilization of endophytic bacteria such as actinobacteria is one of the alternatives to obtain the bioactive compounds similar to the host plant. This study aimed to identify compounds produced by rhizosphere and endophytic actinobacteria isolated from Xylocarpus granatum for their antioxidant and antiglycation activity. Actinobacterial culture supernatant was extracted using ethyl acetate with a ratio of 1:1 (v/v). Antioxidant activity was performed using 2,2-diphenyl-1-picrylhydrazyl (DPPH). Whole TLC-bioautography and phytochemical tests were used to predict the group of active compounds. Antiglycation activity was identified based on the ability to inhibit the formation of advanced glycation end products (AGEs). Fifteen actinobacterial isolates had been isolated from rhizosphere (ten isolates), fruit (two isolates), and leaf (two isolates) of X. granatum. All isolates had been tested for their antioxidant and antiglycation activity. Isolate XR2 had the highest antioxidant activity with IC50 value of 1719.26 mg/L. Meanwhile, the highest antiglycation activity was obtained from isolate XR8 with IC50 value of 327.62 mg/L. This study informs that actinobacteria also live in the fruit, leaves and rhizosphere of X. granatum. The existence of rhizosphere and endophytic actinobacteria from X. granatum and their antioxidant and antiglycation activities contributes to the understanding of their diversity and potency as an antioxidant and antiglycation agent.